An Initial Assessment of the Collembola (Hexapoda) Fauna of the Bula Hyrcanian Forest (Iran) at the Interface of Two Biodiversity Hotspots - Cyrille D'Haese; Masoumeh Shayanmehr; Elham Yoosefi Lafooraki; Thomas Tully (Soil Organisms)
The Hyrcanian Forests of northern Iran, a UNESCO World Heritage Site, are renowned for their exceptional biodiversity, hosting numerous relict, threatened, and endemic species. Located at the intersection of the Caucasus and Irano-Anatolian biodiversity hotspots, these forests have been extensively studied for vascular plants, but soil arthropods like springtails (Collembola) remain largely understudied.